Acoustic properties of liquid 4He measured by Rayleigh-SAW - Aoki, Y; Yamaguchi, W; Wada, Y; Sekimoto, Y; Nomura, R; Okuda, Y (Physica. B, Condensed matter, 2003)
Damping and velocity of Rayleigh surface acoustic waves (SAW) were measured in liquid 4He. A Rayleigh-SAW propagates along the substrate surface by emitting compressional waves into the liquid and thus the damping of the Rayleigh-SAW is determined by the acoustic impedance of the surrounding liquid 4He. Temperature dependence agreed well with the reported values of the impedance and the superfluid transition in 4He was clearly seen. We also set up a reflection plate 1.5 mm above the SAW device which reflected the emission waves. They were converted back into the SAW and used to measure the velocity and damping of ultrasound in liquid 4He separately.